Strategi Pengembangan Usaha Sabut Kelapa di Kabupaten Indragiri Hilir - Herlon, Meki; Rifa’i, Ahmad; Rosnita, Rosnita; Yulida, Roza; Muwardi, Didi; Ridho, Zulhamid; Mustaqim, Mustaqim (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Indragiri Hilir Regency, one of Indonesia’s major coconut-producing regions, faces a structural paradox in which high production volumes have not translated into improved farmer welfare. Dependence on the sale of whole coconuts with low added value, coupled with significant price fluctuations, has led to inefficiencies in the commodity’s economic supply chain. Coconut husk, which has long been neglected and treated as waste, in fact holds substantial economic potential through the development of derivative products. This study aims to analyze the feasibility and formulate effective strategies for developing the coconut husk processing industry in Indragiri Hilir Regency. A qualitative approach was employed using SWOT (Strengths, Weaknesses, Opportunities, Threats) analysis, focusing on the BUMDes Sungai Piyat enterprise group as a case study. The analysis reveals that the coconut husk processing enterprise in Kuala Indragiri District possesses strong and promising internal conditions, with an IFAS score of 2.73 and a strength–weakness differential of 1.91. The main strengths include the abundance of derivative products (coco peat and cocobristle), ease of production processes, and the use of semi-modern technology that enhances efficiency. Meanwhile, the EFAS score of 2.32, with an opportunity–threat differential of 1.48, indicates substantial external support, particularly due to limited competition, sustainable raw material supply, a growing regional economy, and institutional backing. The combination of these scores places the enterprise in Quadrant V (Grow and Build Strategy) of the Internal–External (IE) Matrix, recommending the adoption of an aggressive growth strategy. Key strategic directions include increasing production capacity, expanding market networks, strengthening institutional partnerships, and diversifying value-added products to promote sustainability and enhance contributions to the local economy and the empowerment of coastal communities in Indragiri Hilir.